PENGARUH UMUR TANAMAN KELAPA SAWIT TERHADAP KELIMPAHANSERANGGA PENYERBUK (ELAEIDOBIUS KAMERUNICUS) - Saufiah, Saufiah; Chairudin, Chairudin; Lizmah, Sumeinika Fitria (Universitas Teuku Umar, 2019)
Oil palm plants are a type of plant that undergoes pollination through the mediation of polinator agents because of the position of male flowers and female flowers in separate flowers. Elaeidobius kamerunicus is an effective type of pollinating insect in oil palm plants. This research was conducted at this research carried out on oil palm plantations of PT. Karya Tanah Subur (KTS) of West Aceh Regency. This research was conducted from February to March 2018. The collection of insect samples using the Purpose Sample method (sample determined), which uses 4 blocks of plants with different age groups of 4,5,6 and 7 years, respectively. Each age group on each block uses 6 sample plants. The results show the abundance of pollinator insects not influenced by plant age and altitude, but are influenced by the time of sampling. Domination index of palm oil pollinator insect simpons at PT. Karya Tanah Subur (KTS) is worth 0.9280 which means high evenness. The abundance of oil palm pollinators affects the average production of oil palm at PT. Karya Tanah Subur (KTS) Keywords: oil palm, Elaeidobius kamerunicus, pollinator